Long-Term Chili Monoculture Alters Environmental Variables Affecting the Dominant Microbial Community in Rhizosphere Soil - Chen, Wenjing; Guo, Xiaodong; Guo, Quanen; Tan, Xuelian; Wang, Zhigang (Frontiers in Microbiology, 2021)
Continuous cropping negatively affects soil fertility, physicochemical properties and the microbial community structure. However, the effects of long-term chili monoculture on the dominant microbial community assembly are not known. In this study, the impact of long-term chili monoculture on the correlation between the dominant microbial community and soil environmental variables was assessed. The results indicated that increasing duration of chili monoculture generated significant changes in soil nutrients, soil aggregates and soil enzymes: nutrient contents increased overall, mechanically stable macroaggregates increased and microaggregates decreased, water-stable macroaggregates and microaggregates decreased, β-glucosidase and urease activities decreased nonlinearly, and nitrate reductase and alkaline phosphatase activities showed a nonlinear increase. Moreover, an increasing number of years of chili monoculture also affected the structure of the dominant microbiota, with substantial changes in the relative abundances of 11 bacterial and fungal genera. The drivers of the dominant microbial community assembly in rhizosphere soil were soil moisture, pH and salt.